The effectiveness of the CLEAR module in improving year four pupils’ procedural and conceptual knowledge of fractions titles in urban school - Mokhtar, Azarul; Mohd Ayub, Ahmad Fauzi; Mustakim, Siti Salina; Said, Rozita Radhiah (Human Resource Management Academic Research Society, 2022)
Various heuristic approaches can be used as a solution to mathematical problems, and this study focuses on mnemonic techniques. Fraction is also a difficult topic for pupils to master. This module is known as "CLEAR" (Circle, Line, Evaluate, Answer, Recheck). Therefore, this research aims to determine the effectiveness of the CLEAR module on the students’ cognitive aspects of students. This study adopted the quasi-experimental pre-post-test research design and was conducted in a school. The findings showed that a significant difference between the achievement scores of students who used the CLEAR module compared to students who used the conventional method in the post-test and post-delayed test. This study also found a significant difference in the students’ mean scores for problem-solving skills; students who used the CLEAR module scored higher than students who used the conventional method in the post-test and post-delayed tests. In regard to their conceptual knowledge, there is also a significant difference between the students’ mean scores in the post-test and post-delayed test. In this light, where students of the treatment group had better conceptual knowledge compared to students of the control group. Students who used the CLEAR module showed better conceptual knowledge than students who used the conventional methods. Furthermore, for procedural knowledge, students in the treatment group have shown better procedural knowledge compared to students in the control group in the post-delayed test. The findings on mathematical word problems show that the use of the CLEAR module can improve students’ achievement in the topic of fractions. It indicates that the use of the CLEAR module is suitable for use by teachers to increase students’ interest and achievement in mathematics, especially in the topic of fractions. This study contributes to a new teaching strategy, specifically the modular-based approach as a mathematics T&L practise in primary schools.